Capacitance roll‐off and frequency‐dispersion capacitance–conductance phenomena in field plate and guard ring edge‐terminated Ni/SiO2/4H‐nSiC Schottky barrier diodes. Issue 1 (4th November 2015) - Kumar, Vibhor; Kaminski, Nando; Maan, Anup Singh; Akhtar, Jamil
Abstract : In this work, field plate and guard ring edge‐terminated Ni/4H‐nSiC Schottky barrier diodes (SBD) were fabricated using standard photolithography process. Strange peaks in capacitance–conductance curves, capacitance roll‐off, and a high value of ideality factor ( η = 1.3) in fabricated SBD were seen as a signature of interface trap states ( N ss ) at the residual oxide (2.2 nm)/4H‐nSiC interface and series resistance ( R s ). Schottky capacitance spectroscopic, High–low capacitance–voltage ( C–V ) and forward‐bias current–voltage ( I–V ) techniques, in the frequency range from 100 Hz to 1 MHz, determines N ss of the order of 10 12 cm −2 eV −1 and were found exponentially distributed in the bandgap of SiC. Using Hill–Coleman's method, the density N ss was calculated to be 1.15 × 10 15 cm −2 eV −1 at 100 Hz and 7.81 × 10 12 cm −2 eV −1 at 1 MHz, which explains the larger value of capacitance at low frequencies. Relaxation times and capture cross sections of N ss were also estimated. Calculated values of N ss were used in a Silvaco simulation that emphasize that bulk level defects present in the SiC also contributes in the experimentally observed strange peaks in C–V characteristics of fabricated SBD. At higher current levels, calculated values of R s ( V, f ), confirm an increase of leakage current through residual oxide and describes the capacitance roll‐off phenomena in the fabricated SBD.